TRANSFORMASI DIGITAL BPR MELALUI INFLUENCER MARKETING PADA PLATFORM TIKTOK: MODEL KOLABORASI STRATEGIS UNTUK MENINGKATKAN BRAND AWARENESS, LITERASI KEUANGAN, DAN AKSESIBILITAS LAYANAN KEUANGAN MIKRO DI ERA KONTEN VIRAL - GHAZIYAH NAILATUL FAIZAH (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2026)
This study discusses the implementation of a collaboration strategy between Rural Banks (BPR) and TikTok content creators as part of digital transformation efforts to expand access to microfinance services. Amid the rapid growth of the digital economy and the rise of viral content trends, microfinance institutions face challenges in reaching a new generation that is more responsive to visual and informative communication on social media. This study analyzes how the TikTok platform, through partnerships with influencers, can be utilized to increase brand awareness, improve public financial literacy, and expand access to financial products. Using a qualitative method through a literature study, this research collects data from various credible sources. The results indicate that this strategy can increase brand awareness by up to 37%, improve understanding of microfinance products by 42%, and reach market segments that were previously difficult to access. This study recommends that BPR utilize the unique characteristics of TikTok, such as short-form content, authentic delivery style, and an educational approach, in developing innovative and inclusive digital marketing strategies.